Metode Image Pasting Sebagai Upaya Peningkatan Life Skill pada Anak Down Syndrome - Eka Sufartianinsih Jafar; Alfiah Ramdani; Utami Lesty Maulana; Yunis Liana Galib; Andi Lilis Dwi Nurabdillah (Universitas Negeri Makassar, 2023)
This study aims to teach Down syndrome children strategies for improving daily life skills. Life skills that can increase independence are carrying out activities that are effective and not monotonous. An effective strategy that can help children with Down syndrome is being able to have an approach and attachment to their parents, and have an awareness of the independence that must be exercised. One strategy is to use the image paste method. Paste pictures is a method that is done by pasting and providing pictures that are concrete, interesting, and easily understood by children with Down syndrome. The images given are in the form of activities carried out in everyday life. Each picture will be pasted on the sides of the walls in each child's room according to the activity being carried out. This method aims to increase the cognitive stimulation of children with Down syndrome in increasing independence from an early age as a provision for the future. The purpose of this activity is to find out strategies for improving the life skills of children with Down syndrome at the Secretariat of the Community of Parents and Children with Down Syndrome, South Sulawesi. This research uses descriptive research with a qualitative approach. Data collection was carried out using data from interviews, observations, and documentation of children with Down syndrome before and after the activity was carried out. The results show that giving picture stickers can improve life skills strategies for children with Down syndrome in everyday life.